Editorial: Biosafety and Biosecurity Approaches to Counter SARS-CoV-2: From Detection to Best Practices and Risk Assessment Volume 2 - Pillai, Segaran P.; Morse, Stephen A. (Frontiers in Bioengineering and Biotechnology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) is the causative agents of Coronavirus Disease-19, commonly referred to as COVID-19. SARS-CoV- 2 was discovered in 2019 and is currently responsible for a global pandemic that has resulted in more than 642.7 million cases and 6.625 million deaths worldwide as of November 19th, 2022. Since the pandemic associated with SARS-CoV-2 began, countless laboratories around the world have switched their research priorities to focused on the origin of the virus, its pathogenicity, development of vaccines and medical countermeasures such as anti-virals, immune globulins, rapid diagnostics and detection technologies, surveillance efforts and the monitoring of genetic changes and the emergence of new variants. The latter includes Alpha (B.1.1.7 and Q lineages), Beta (B.1.351 and descendent lineages), Gamma (P.1 and descendent lineages), Delta (B.1.617.2 and AY lineages), Epsilon (B.1.427 and B.1.429), Eta (B.1.525), lota (B.1.526), Kappa (B.1.617.1), 1.617.3, Mu (B.1.621 and B.1.621.1), Zeta (P.2) and B.1.617.3 variants which are being monitored as well as variants of concern which includes Omicron (B.1.1.529, BA.1, BA.1.1, BA.2, BA.3, BA.4 and BA.5 lineages) (CDC). The current observation of the virus’s ability to mutate and adapt begs the need for enhanced biosafety and biosecurity measures to ensure that the laboratory work being performed does not contribute to accidentally introduction into the community. To ensure this, there is a need for laboratories conducting such work to perform risk assessments and implement appropriate risk mitigation strategies along with safe and best laboratory practices leveraging engineering and administrative controls, personal protective equipment, etc.